2009
DOI: 10.1111/j.1365-2729.2008.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning to collaborate by collaborating: a face‐to‐face collaborative activity for measuring and learning basics about teamwork1

Abstract: In today's fast-changing business environment, teams have emerged as a requirement for business success. However, in schools and universities, students are usually not taught teamwork skills. In this paper, we introduce learning to collaborate by collaborating, a process that enables collaboration and teamwork skills to be taught and measured through face-to-face collaborative work and class-wide activities supported by wirelessly connected hand-held devices. Following a description of learning to collaborate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 26 publications
0
27
0
8
Order By: Relevance
“…The originality of our research reveals possibilities for improving and using RPGs to teach many different health science courses. We believe that this methodology gives the students the opportunity to understand and acquire the skills that underlie simple specific knowledge acquisition, such as working in a team 46,47 , conflict resolution 48,49 and problem solving by peer discussion 36,50,51 . This study revealed some of the limitations of cooperative learning.…”
Section: Discussionmentioning
confidence: 99%
“…The originality of our research reveals possibilities for improving and using RPGs to teach many different health science courses. We believe that this methodology gives the students the opportunity to understand and acquire the skills that underlie simple specific knowledge acquisition, such as working in a team 46,47 , conflict resolution 48,49 and problem solving by peer discussion 36,50,51 . This study revealed some of the limitations of cooperative learning.…”
Section: Discussionmentioning
confidence: 99%
“…Other earlier initiatives include using Web log data generated by course management systems (e.g. WebCT) to help instructors become aware of students' activities in distance learning classes [13]; or class-wide collaborative activities supported by hand-held devices [2]. However, with the notable exception of a few works, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…When learning with others, students are able to learn more because of the process of achieving a shared understanding during the development of the activity (Cortez, Nussbaum, Woywood, & Aravena, 2009). Thus, teamwork becomes a positive learning experience while it inspires genuine cooperation among students.…”
Section: Discussionmentioning
confidence: 99%